Glutathione Regulates GPx1 Expression during CA1 Neuronal Death and Clasmatodendrosis in the Rat Hippocampus following Status Epilepticus - Ji-Eun Kim; Duk-Shin Lee; Tae-Hyun Kim; Tae-Cheon Kang (MDPI AG, 2022)
Glutathione peroxidase-1 (GPx1) catalyze the reduction of H2O2 by using glutathione (GSH) as a cofactor. However, the profiles of altered GPx1 expression in response to status epilepticus (SE) have not been fully explored. In the present study, GPx1 expression was transiently decreased in dentate granule cells, while it was temporarily enhanced and subsequently reduced in CA1 neurons following SE. GPx1 expression was also transiently declined in CA1 astrocytes (within the stratum radiatum) following SE. However, it was elevated in reactive CA1 astrocytes, but not in clasmatodendritic CA1 astrocytes, in chronic epilepsy rats. Under physiological condition, L-buthionine sulfoximine (BSO, an inducer of GSH depletion) increased GPx1 expression in CA1 neurons but decreased it in CA1 astrocytes. However, N-acetylcysteine (NAC, an inducer of GSH synthesis) did not influence GPx1 expression in these cell populations. Following SE, BSO aggravated CA1 neuronal death, concomitant with reduced GPx1 expression. Further. BSO also lowered GPx1 expression in CA1 astrocytes. NAC effectively prevented neuronal death and GPx1 downregulation in CA1 neurons, and restored GPx1 expression to the control level in CA1 astrocytes. In chronic epilepsy rats, BSO reduced GPx1 intensity and exacerbated clasmatodendritic degeneration in CA1 astrocytes. In contrast, NAC restored GPx1 expression in clasmatodendritic astrocytes and ameliorated this autophagic astroglial death. To the best of our knowledge, our findings report, for the first time, the spatiotemporal profiles of altered GPx1 expression in the rat hippocampus following SE, and suggest GSH-mediated GPx1 regulation, which may affect SE-induced neuronal death and autophagic astroglial degeneration.